2007
DOI: 10.1051/0004-6361:20077810
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of chiral symmetry restoration and random orientation of galaxies

Abstract: We studied the chiral symmetry restoration and the spatial orientation of 2288 spiral and spiral barred galaxies that have radial velocities (RV) less than 5000 km s −1 . A random direction of the rotation of galaxies is assumed in order to classify the structural modes. The distribution of spin vector and spin vector projections of leading and trailing arm galaxies in the total sample and subsamples are studied. We use chi-square, auto-correlation and Fourier tests in order to discriminate the preferred align… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…In general, our results support Hierarchy model. The spatial orientation of galaxies in 117 clusters were studied till date 12,13,14,15,16,17,18,19,20,21 . In most cases no preferred alignment is noticed (Hierarchy model).…”
Section: Resultsmentioning
confidence: 99%
“…In general, our results support Hierarchy model. The spatial orientation of galaxies in 117 clusters were studied till date 12,13,14,15,16,17,18,19,20,21 . In most cases no preferred alignment is noticed (Hierarchy model).…”
Section: Resultsmentioning
confidence: 99%
“…Here we describe the procedure for the removal the selection effects to obtain the isotropic distributions for both and as given by Aryal & Saurer [1][2][3][4][5][6][7]. Theoretically, the isotropic distribution curve for polar angle is cosine and that for azimuthal angle is the average distribution curve, with the restriction that the database is free from selection effect.…”
Section: Methods Of Analysismentioning
confidence: 99%
“…Godlowski et al (2003) showed that Li model predicts the existence of a vanishing angular momentum [8]. Their prediction was observationally tested by several authors [9][10][11][12][13][14][15][16][17][18] and found the vanishing angular momenta for less massive structures (galaxy groups, poor galaxy clusters, etc) and non-vanshing angular momenta for larger structures (compact groups, rich galaxy clusters, etc). Therefore, it is essential to probe the angular momenta of galaxy clusters directly based on dynamical analysis.…”
Section: Introductionmentioning
confidence: 99%